Eco-innovation and firm growth: Do green gazelles run faster? Microeconometric evidence from a sample of European firms - Alessandra Colombelli; Jackie Krafft; Francesco Quatraro (WWWforEurope, 2015)
This paper investigates the impact of eco-innovation on firms growth processes, with a special focus on gazelles, i.e. firms showing higher growth rates than the average. In a context shaped by more and more stringent environmental regulatory frameworks, we posit that inducement mechanisms stimulate the adoption of green technologies, increasing the derived demand for technologies produced by upstream firms supplying eco-innovations. For these reason we expect the generation of green technologies to trigger sales growth. We use firm-level data drawn from the Bureau van Dijk Database, coupled with patent information obtained from the OECD Science and Technology Indicators. The results confirm that eco-innovations are likely to augment the effects of generic innovation on firms growth, and this is particularly true for gazelles, which actually appear to run faster than the others.
Keywords: L10; L20; O32; O33; Q53; Q55; 330; Gazelles; Eco-Innovation; firms growth; Inducement mechanisms; derived demand; WIPO Green Inventory